What Is The Prevalence of The Adverse Effects of Oxygen Therapy Administered During Acute Exacerbations of Chronic Obstructive Pulmonary Disease? - Jennings, Lise-Anne (2008)
BACKGROUND Breathless patients, as seen in exacerbated COPD, need oxygen, but giving too high a flow rate of oxygen to a patient dependent on a degree of hypoxia to drive their respiration can reduce their respiratory drive, resulting in carbon dioxide retention and may precipitate respiratory arrest (Booker, 2005 & NCCCC, 2004). However, this theory is debated in the research literature. The adverse effects were known, but there was little evidence into the prevalence of the adverse effects. Therefore, the aim of this dissertation was to establish the prevalence of adverse effects of oxygen therapy in acute exacerbations of COPD.